USE OF STANDING FOOTS REFLECTION DEVICES TO REDUCE PAIN IN CANCER PATIENTS DURING CHEMOTHERAPY (Proceedings OPTIMAL, 2026)
Chemotherapy in cancer patients has many detrimental side effects, but this treatment remains a medical option. While chemotherapy is the primary treatment option for cancer, peripheral neuropathy, which refers to nerve damage that can develop as a result of chemotherapy, is often present. Non-pharmacological interventions are needed to ensure that cancer patients can lead a quality life without pain after chemotherapy. The Standing Foot Reflection Device (SFRD) is a device with acupressure points that is expected to be effective in reducing pain. The Standing Foot Reflection Device (SFRD) is effective in reducing moderate to imperceptible pain levels.The purpose of this study was to determine the effect of the use of the Standing Foot Reflection Device (SFRD) on pain during chemotherapy in cancer patients at the Indonesian Cancer Foundation. Using a quantitative method with a quasi-experiment, designed by involving a control group in addition to the intervention group that allows researchers to test the changes that occur through a pretest and posttest design with a control group. The results of the univariate analysis obtained were 51% pre-elderly, including women (68%), who worked (62%), with Diploma-III/S-1 education as much as 43%. The results of the bivariate analysis, the p-value chi square pretest of the intervention and control groups could not be calculated because many cells were empty. While the p-value of chi square posttest = 0.000 (